(untitled) (Academic Journal of International University of Erbil, 2025)
Marital status is a significant dimension since it is connected with the job performance of banking sector employees and different maintenance factors. The present study is an attempt to highlight the impact of marital status on the performance of bank employees, with gender playing a mediating role. Four private banks were selected for this research to collect data from 160 employees. All these banks are from the Nagpur region of Maharashtra, India. For this study, both types of data (secondary and primary) were used. The data was gathered using a simple random sampling technique. A questionnaire was used as an instrument to accumulate data from the respondents. After a detailed literature study, two objectives and a hypothesis were framed. Statistical analyses were done to achieve the objectives, such as the normality test, reliability test, Mann-Whitney test, and regression analysis. It was concluded that married bank employees perform better than unmarried employees and, hence, have higher job performance. Additionally, it was found that males perform their work much better than females.